To solve the equation \(-3x - 6 = 18\) for \(x\), follow these steps in the correct order:
1. Add 6 to both sides of the equation to isolate the term with \(x\):
\[
-3x - 6 + 6 = 18 + 6
\]
Simplifying this gives:
\[
-3x = 24
\]
2. Divide both sides by -3 to solve for \(x\):
\[
\frac{-3x}{-3} = \frac{24}{-3}
\]
Simplifying this gives:
\[
x = -8
\]
So, the steps in order are:
1. Add 6 to both sides.
2. Divide both sides by -3.
Thus, \(x = -8\).
Drag the correct steps into order to solve the equation -3x – 6 = 18 for x.
1 answer